Some reflections on the state of development economics in Asia - Hill, Hal; Jayasuriya, Sisira (2019)
This paper reviews some salient aspects of the state of development economics, from the early post-war pioneers through the major 1989 survey by Nicholas Stern, to contemporary experiences and lessons. The latter is illustrated with references to five South and Southeast Asian countries. While the techniques of economic analysis have become ever more sophisticated and the data bases larger and richer, significant analytical puzzles remain. The central question of why some countries perform well and others indifferently is still imperfectly understood. Because many factors—economic, political, institutional, as well as random events— shape countries’ development trajectories, country economic forecasting over the medium to longer run continues to be as much art as science.
Keywords: Development economics -- Asia